Microbial contamination of anesthetic syringes in relation to different handling habits - Heid, Florian; Bender, Carolin; Gervais, Hendrik; Schmeck, Joachim; Kohnen, Wolfgang; Noppens, Rüdiger (American journal of infection control, 2016)
This single-center study prospectively assessed the microbial contamination of anesthetic syringes handled perioperatively under different conditions. We documented high rates of bacterial contamination, with strong but statistically nonsignificant differences between handling groups. Our results identify skin contact as the main source of contamination, and thus we emphasize the impact of proper hand hygiene.